Determinants of self-care practices in patients with breast cancer-related upper limb lymphedema: a cross-sectional analysis - Zhongru Cao; Hongbo Huo (Frontiers in Public Health, 2026)
Objective To assess the level of self-care practices among patients with BCRL and explore factors associated with these practices. Methods A total of 137 patients with BCRL who received treatment at our hospital between April 2022 and 2023 were included in this study. All participants met the predefined inclusion and exclusion criteria. Data were collected using a general information questionnaire, the Self-Care Behavior Scale for BCRL Patients, the Lymphedema Limb Function-Disability-Health Scale, and the Lymphedema Health Belief Questionnaire. Results The total self-care behavior score of patients with BCRL was 71.69 ± 7.42, with a score index of 74.68%. The total limb function-disability-health score was 105.61 ± 35.76, with a score index of 32.92%. The total health belief score was 99.68 ± 11.23, with a score index of 79.74%. Hierarchical regression analysis showed that age, body mass index (BMI), surgical approach, total limb function-disability-health score, and total health belief score were significantly associated with self-care behavior ( P < 0.05). Conclusion Self-care practices among patients with BCRL were moderate and require further improvement. Age, BMI, surgical approach, upper limb function-disability-health status, and health belief level were associated with self-care behavior. Given the cross-sectional design, these findings should be interpreted as associations rather than causal relationships. Healthcare professionals should assess patients' upper limb function and health beliefs and provide targeted health education, rehabilitation guidance, and self-management support to improve self-care practices and quality of life in this population.